Exploring the Perceived Effectiveness of HIV and AIDS Related Messages among Key Populations: A Descriptive Phenomenological Study (Surkhet Journal, 2025)
The HIV epidemic among key populations in Nepal, including sexual minorities and female sex workers, has not shown the expected decline despite targeted communication campaigns. To better understand the perceptions of these key populations regarding the effectiveness of HIV and AIDS-related messages, a descriptive phenomenological study was conducted in the Banke district. This study utilized in-depth interviews with nine participants selected through snowball sampling from these key populations, as well as two focus group discussions with purposively selected additional participants, all of whom were between the ages of 20 and 40 and were already exposed to the messages. Data were analyzed using Colaizzi's descriptive phenomenological analysis method. The findings of this study indicate that HIV and AIDS-related messages were successful in enhancing awareness and changing attitudes and behaviors related to HIV and AIDS among the participants. These messages increased self-esteem and risk perception, as well as facilitated the adoption of safer sex practices and the utilization of available HIV and AIDS care. Additionally, the participants developed a positive attitude towards people living with HIV (PLHIV) and engaged in information-seeking and peer-support behaviors related to HIV and AIDS. While these results suggest that the messages were effective from the participants' perspectives, further research is required to explore the coverage of the communication programs and identify additional strategies that may be effective in reducing the HIV epidemic in these populations.